Concepts, utilization, and perspectives on the Dutch Nationwide Trauma registry: a position paper. - Hoepelman, R. J.; Driessen, M. L. S.; de Jongh, M. A. C.; Houwert, R. M.; Marzi, I.; Lecky, F.; Lefering, R.; van de Wall, B. J. M.; Beeres, F. J. P.; Dijkgraaf, M. G. W.; Groenwold, R. H. H.; Leenen, L. P. H. (European Journal of Trauma & Emergency Surgery, 2023)
Over the last decades, the Dutch trauma care have seen major improvements. To assess the performance of the Dutch trauma system, in 2007, the Dutch Nationwide Trauma Registry (DNTR) was established, which developed into rich source of information for quality assessment, quality improvement of the trauma system, and for research purposes. The DNTR is one of the most comprehensive trauma registries in the world as it includes 100% of all trauma patients admitted to the hospital through the emergency department. This inclusive trauma registry has shown its benefit over less inclusive systems; however, it comes with a high workload for high-quality data collection and thus more expenses. The comprehensive prospectively collected data in the DNTR allows multiple types of studies to be performed. Recent changes in legislation allow the DNTR to include the citizen service numbers, which enables new possibilities and eases patient follow-up. However, in order to maximally exploit the possibilities of the DNTR, further development is required, for example, regarding data quality improvement and routine incorporation of health-related quality of life questionnaires. This would improve the quality assessment and scientific output from the DNTR. Finally, the DNTR and all other (European) trauma registries should strive to ensure that the trauma registries are eligible for comparisons between countries and healthcare systems, with the goal to improve trauma patient care worldwide.